A Single Consumption of High Amounts of the Brazil Nuts Improves Lipid Profile of Healthy Volunteers - Elisângela Colpo; Carlos Dalton de Avila Vilanova; Luiz Gustavo Brenner Reetz; Marta Maria Medeiros Frescura Duarte; Iria Luiza Gomes Farias; Edson Irineu Muller; Aline Lima Hermes Muller; Erico Marlon Moraes Flores; Roger Wagner; João Batista Teixeira da Rocha (Journal of Nutrition and Metabolism)
Background. This study investigates the effects of Brazil nut ingestion on serum lipid profile in healthy volunteers. Methods. Ten healthy subjects were enrolled in the study. Each subject was tested 4 times in a randomized crossover in relation to the ingestion of different serving sizes of the Brazil nut: 0, 5, 20, or 50 g. At each treatment point, peripheral blood was drawn before and at 1, 3, 6, 9, 24, and 48 hours and 5 and 30 days. Blood samples were tested for total cholesterol, high- and low-density lipoprotein cholesterol (HDL-c and LDL-c, resp.), triglycerides, selenium, aspartate and alanine aminotransferases, albumin, total protein, alkaline phosphatase, gamma GT, urea, creatinine, and C-reactive protein. Results. A significant increase of the plasma selenium levels was observed at 6 hours within the groups receiving the nuts. Serum LDL-c was significantly lower, whereas HDL-c was significantly higher 9 hours after the ingestion of 20 or 50 g of nuts. The biochemical parameters of liver and kidney function were not modified by ingestion of nuts. Conclusions. This study shows that the ingestion of a single serving of Brazil nut can acutely improve the serum lipid profile of healthy volunteers.